2020
DOI: 10.1016/j.actamat.2020.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding grain nucleation under Additive Manufacturing solidification conditions

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…It is well known that the fraction of thermal undercooling increases with the increased cooling rate. It is reported that the fraction of thermal undercooling becomes approximately 80% at a cooling rate of 100 K/s and a temperature gradient of 1000 K/m for the Al-Cu alloy [36]. Figure 12 qualitatively agrees with this relation.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…It is well known that the fraction of thermal undercooling increases with the increased cooling rate. It is reported that the fraction of thermal undercooling becomes approximately 80% at a cooling rate of 100 K/s and a temperature gradient of 1000 K/m for the Al-Cu alloy [36]. Figure 12 qualitatively agrees with this relation.…”
Section: Resultssupporting
confidence: 71%
“…The results at 10 4 K/s were close to those obtained by the Scheil model, except for the initial undercooling period. Thermal undercooling corresponded to the majority of the solidification interfaces at an increasing cooling rate [36]. Thus, the growth rate under a higher cooling rate accelerated in the early stage and strongly decelerated as it neared the local equilibrium at the interface in the final stage.…”
Section: Resultsmentioning
confidence: 92%
“…[27,28] It is important to note that V is sometimes denoted as R, as the growth rate of the S/L interface, which is the microstructure response to the isotherm velocity or pull rate. While there is an important difference between the two, [29] in this paper, we are not differentiating the two as they are closely linked. Recent results show that CET can be achieved in some alloys by decreasing G in the liquid region and increasing V without adding alloying elements.…”
Section: Metal Fusion Additive Manufacturing (Am) Ismentioning
confidence: 94%
“…This suggests a much greater contribution of thermal undercooling to facilitate nucleation on less favorable grains. [29] This means that while at lower V, the solute is a dominant player in providing the required undercooling [5] ; it is the thermal undercooling that acts as a nucleation multiplier at high V and high G. With shorter NFZ at high V and steep G, the role of solute is restricted. This implies that alloys of two different compositions with the same inoculant chemistry and of similar size distribution would be expected to trigger an equally large number of equiaxed nucleation events.…”
Section: B Modification Of the Interdependence Model To Ammentioning
confidence: 99%
“…In the L-PBF process, the heating and cooling rates range from 10 3 to 10 6 K/s. [26,48] Due to the limited melting time caused by the high scanning speed of the heating source, a much higher heating temperature is required to eliminate the balling behavior induced by the cage effect. However, severe overheating of the metallic powder can inevitably raise the evaporation of low melting point solutes and affect the mechanical performance of the as-built component.…”
Section: B the Delayed Fully Melting Temperaturementioning
confidence: 99%